The upbringing of working children: considerations from the standpoint of public health - Jáider Otálvaro O (Universidad de Antioquia, 2011)
This paper seeks to contribute to the current discussion about the nature and disciplinary position of public health in regards to child labor. Due to its magnitude, consequences, and the way in which it becomes a daily living situation for children and adolescents, both social sciences and public health are becoming increasingly interested in this phenomenon. This paper proposes a conceptual and epistemological problematization using different approaches which aims at explaining the phenomenon of child labor from the point of view of public health and governmental and non-governmental organizations. Furthermore, a conceptual alternative is proposed which approaches the issue of child labor from categories such as nurturing, human development, alternative public health, and narrative research. The latter is considered as a methodological and epistemological current that overcomes some limitations found in abolitionism and protectionism, two currents that have tried to approach and to explain child labor.